The Quality of Services in Medical Tourism and the use of TIC (Global Journal of Human-Social Science, 2021)
Offering quality services has become a great advantage to attract customers, mainly service companies that operate in dynamic and competitive environments such as medical tourism, which is why it is important that they adapt to current changes and trends, each It is increasingly necessary to incorporate new technological tools to be at the forefront. This is an applied research with a quantitative, descriptive approach, and its purpose is to identify the variables that affect the quality of the service and the use of Information and Communication Technologies (ICT) by companies dedicated to medical tourism. The Servperf Model instrument was adapted, and through a factor analysis, the variables of tangibility, reliability, responsibility, security and empathy were analyzed to identify which ones affect the perception of quality of services and determine if there is a correlation between them. The findings indicated that ICT play a relevant role in the quality of service since they generate a competitive advantage, more and more customers use technologies in their daily activities, therefore, they are more informed and more demanding with the services they expect to obtain.
Keywords: medical tourism; quality of service; information and communication technologies